Strengthen the application research of big data in food safety - Qi TAO; Xiaohui CUI (Zhongguo shipin weisheng zazhi, 2020)
Food safety is essential to national economy and people's livelihood. A good food safety system is extremely important for maintaining social stability and providing scientific data for government decision. Big data provides a new approach to food safety. Through the integration of the data in the whole industrial chain, it will greatly improve the data analysis ability and help in discovering the potential valuable information. It could provide scientific decision-making suggestions for regulators, producers and consumers. It will provide a solution for timely warning of food safety incidents, the accurate traceability and accountability of food products. This paper will briefly introduce some existing big data platforms in food safety area. Then, it will discuss the challenges such as multi-sources data analysis, visualization and market mechanism. At the end of this paper, the future development trend of big data in food safety area is discussed.